Giant anomalous Nernst effect and quantum-critical scaling in a ferromagnetic semimetal. Issue 11 (November 2018) - Sakai, Akito; Mizuta, Yo; Nugroho, Agustinus; Sihombing, Rombang; Koretsune, Takashi; Suzuki, Michi-To; Takemori, Nayuta; Ishii, Rieko; Nishio-Hamane, Daisuke; Arita, Ryotaro; Goswami, Pallab; Nakatsuji, Satoru
Abstract In conducting ferromagnets, an anomalous Nernst effect—the generation of an electric voltage perpendicular to both the magnetization and an applied temperature gradient—can be driven by the nontrivial geometric structure, or Berry curvature, of the wavefunction of the electrons1, 2 . Here, we report the observation of a giant anomalous Nernst effect at room temperature in the full-Heusler ferromagnet Co2 MnGa, an order of magnitude larger than the previous maximum value reported for a magnetic conductor3, 4 . Our numerical and analytical calculations indicate that the proximity to a quantum Lifshitz transition between type-I and type-II magnetic Weyl fermions5–7 is responsible for the observed –T log(T ) behaviour, withT denoting the temperature, and the enhanced value of the transverse thermoelectric conductivity. The temperature dependence of the thermoelectric response in experiments and numerical calculations can be understood in terms of a quantum critical-scaling function predicted by the low-energy effective theory over more than a decade of temperatures. Moreover, the observation of an unsaturated positive longitudinal magnetoconductance, or chiral anomaly8–10, also provides evidence for the existence of Weyl fermions11, 12 in Co2 MnGa. A magnetic field and temperature gradient produce a large electric potential in a ferromagnet, indicating the possible presence of Weyl points. The specific structure of Weyl points gives the electrons quantum-critical properties.